Genome-wide association study for compactness traits in oil palm (Elaeis guineensis Jacq.) - Samsudin, Amer Izzat; Vetaryan, Sharmilah; Ahmad Mohktar, Mohd Azinuddin; Abdul Rahim, Muhamad Farid; Ting, Ngoot Chin; Zolkafli, Siti Hazirah; Singh, Rajinder; Ramlee, Shairul Izan; Lee, Yang Ping (Springer Science and Business Media B.V., 2025)
Breeding for oil palm with a compact architecture is beneficial, as it facilitates harvesting and enhances yield in commercial plantations through high-density planting. In this study, we conducted a genome-wide association study to identify markers associated with nine compactness traits across a total of 475 Tenera palms from eight biparental families, each containing 42–78 offsprings. These families were derived from the Deli, Nigeria, and Yangambi genetic backgrounds. A Q-matrix of K = 6 was used as a fixed effect to account for population structure. As a result, a total of 27 single nucleotide polymorphism (SNP) markers linked to seven of the nine traits examined, including rachis length, petiole width, petiole depth, and petiole cross-section were successfully identified. Given the complex nature of the traits, SNP markers with small genetic effects were generally identified, and these have the potential to accelerate the introgression of desirable alleles into commercial lines. Among these, seven SNPs co-localised to similar regions with markers identified in previous studies, whereas the remaining markers are novel and can offer important insights into the development of compact palms. Additionally, our findings provide a foundation for further research to uncover the genes responsible for the compactness traits in oil palm.